DIGITALISASI MANAJEMEN PENDIDIKAN - Ahmad Syaifullah; Rofii; Ifah Khadijah; Usep Suherman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digitization of education management is an effort to utilize digital technology in the management process of educational institutions to improve the effectiveness, efficiency, transparency, and quality of educational services. This article aims to explain the concept of digitization of education management, its benefits, challenges, and implementation in school and college administration activities. The method used in writing this article is a literature study by examining various relevant scientific sources, journals, and books. The results of the study show that the digitization of education management is able to facilitate the management of academic data, student administration, school information systems, communication between schools and parents, and data-based decision-making. In addition, the use of digital technology also supports the creation of learning that is more innovative and adaptive to the times. However, the implementation of digitalization still faces several obstacles, such as limited infrastructure, low digital literacy, and lack of human resource readiness. Therefore, policy support, training, and the development of technological facilities are needed so that the digitization of education management can run optimally and sustainably. Keywords: digitalization, education management, educational technology, information systems, educational administration.